The double helix structure of DNA : James Watson, Francis Crick, Maurice Wilkins, and Rosalind Franklin - Albright, R. N. (Revolutionary discoveries of scientific pioneers., 2014)
Discusses the lives and scientific achievements of James Watson, Francis Crick, Maurice Wilkins, and Rosalind Franklin, who all contributed to unraveling the secrets of DNA.